FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGAN PARIWISATA DESA MELALUI DIGITALISASI : SYSTEMATIC LITERATURE REVIEW - Evanne, Lovia (Prospect Publishing, 2025)
Tourism is one sector that needs attention for growth because it has an important role in improving the economic and social level of society. Village Tourism is supported by digitalization to promote villages to the world community. This research aims to determine the theory used in developing village tourism through digitalization and the factors that influence the development of village tourism through digitalization. The method used in this research is a systematic literature review with PRISMA. A theoretical review of relevant articles related to tourism development focuses on actor network theory. The findings of this research are the factors that influence the development of village tourism through digitalization, namely slow tourism, involvement of local communities, adoption of digital technology, collaboration between triple helix village and penta helix, as well as local communities, AI, technology user behavior, tourism rituality/subjective vitality, destination branding strategy, new tourism products, collaboration with other villages, digital divide, social innovation, agrotourism supply chain and integration between AI and big data. Policy implications for participation and collaboration between stakeholders and actors in the use of digitalization. This follows the development of the digital era and synergizes with digitalization. A strong and effective network will accelerate surfing tourism products in the world.